Sistem Inkubasi Mikroklimat dengan Kendali Proporsional dan Pemantauan IoT untuk Aklimatisasi Bibit Dendrobium - Al Barra Harahap; Vera Khoirunisa; Nauval Abi Sopian; Ahmad Rasya Mahfud (Jurnal Otomasi Kontrol dan Instrumentasi, 2026)
Dendrobium orchid seedlings transferred from in vitro culture require stable microclimate conditions during acclimatization, particularly temperature, humidity, and photoperiod regulation, to improve adaptation to non-aseptic environments. However, quantitative evaluations of laboratory-scale incubation systems under constrained actuation conditions remain limited. This study presents a compact microclimate incubation system implementing proportional-only temperature control using fan-based unidirectional cooling, scheduled irrigation and lighting, and real-time IoT monitoring through a Node-RED dashboard. The system was developed using an ESP32-S3 controller and DHT22 sensors in a semi-enclosed multi-tier rack with a capacity of 360 seedling pots. Sensor calibration showed strong agreement with a reference instrument, achieving R² > 0.99 for temperature and humidity measurements. Temperature regulation at a reference value of 29.3 °C achieved a steady-state mean absolute error of 0.1 °C within a deviation range of −0.5 to +0.1 °C during 572 minutes of continuous operation, while maintaining all measurements within ±2 °C of the thermal tolerance range for Dendrobium acclimatization. Increasing proportional gain from  = 1000 to 2550 reduced the reference entry time from 362 s to 208 s. These findings demonstrate that proportional-only control with constrained cooling actuation can provide stable temperature regulation for compact indoor incubation systems.